Embedding Digital Finance in e-Commerce Platforms during the COVID-19 Pandemic : Early Assessment of the Impact of COVID-19 on e-Commerce and the Provision of Digital Financial Services for Micro, Small, and Medium Enterprises and Low-Income Consumers - World Bank (World Bank, Washington, DC, 2021)
This study provides an early assessment of the impact of Coronavirus (COVID-19) on e-commerce platforms and digital financial services, identifying the opportunities, good practices, and key challenges that have emerged in different regions. The focus of the study is to evaluate the impact of Coronavirus (COVID-19) on the use of e-commerce platforms across different regions and the role that digital financial services have played in the process. The emphasis is on digital and financial inclusion of consumers and small businesses and their impact on job creation and economic growth.